<The> Influence of Germany on the Formation of the European Commission in 21St Century - Koszel, Bogdan
Analýza prvého funkčného obdobia Josého Manuela Durãa Barrosa (2004 - 2009) a druhého funkčného obdobia Barrosa (2009 - 2014). Komisia Jeana Clauda Junckera (2014 - 2019). Manfred Weber a Ursula von der Leyen.